High frequency of heterozygous rare variants of the SLC34A1 and SLC9A3R1 genes in patients with atypical femur fracture. Issue 1 (13th January 2023) - Marini, Francesca; Giusti, Francesca; Marasco, Elena; Xumerle, Luciano; Kwiatkowska, Katarzyna Malgorzata; Garagnani, Paolo; Biver, Emmanuel; Ferrari, Serge; Iolascon, Giovanni; Iantomasi, Teresa; Brandi, Maria Luisa
Abstract: Objective: Atypical femur fractures (AFFs) are rare fragility fractures originating at the lateral cortex of the femur, affecting the subtrochanteric or diaphyseal area of thebone with a transverse morphology. Occurrence of AFF is specifically associated with a small number of rare monogenic congenital metabolic bone disorders, such as hypophosphatasia, and with long-term treatment with antiresorptiondrugs. The exact pathogenesis of these fractures remains poorly understood and, except for cases of diagnosed HPP or other AFF-causing bone diseases, it is not possible to assess which patients are at higher riskof developing AFFs as a consequence of anti-resorption therapy. Design: We genetically screened 25 unrelated patients who had developed at least one AFF. Intervention: Genetic screening was performed through a nextgeneration sequencing analysis with a customized panel containing 76 human genes involved in the regulation of the mineralization processWe genetically screened 25 unrelated patients who had developed at least one AFF. Results: We found a relatively high frequency (32.0%) of heterozygous rare variants inthe SLC34A1 and SLC9A3R1 genes, two genes whose heterozygous inactivating mutations have been respectively associated with autosomal dominant hypophosphatemic nephrolithiasis/osteoporosis types 1 and 2 (NPHLOP1and NPHLOP2). Other heterozygous rare variants were found in the BMPR1B, CYP27B1, FBN1, MEPE, PIGO, and PHOSPHO1 genes, each in a single AFF case (4.0%). Conclusions and relevance: Our findings suggest that rarevariants of SLC34A1 and SLC9A3R1 could represent a possible genetic risk factor for the occurrence of AFFs. On the other hand, AFFs could represent an unsuspected clinical manifestation and/or an anti-resorption therapycorrelatedadverse event in patients with NPHLOP disorders.